Professor Valerian Ill'ich Tatarskii – an appreciation. Issue 1 (2nd January 2020) - Brown, G.; Charnotskii, M.; Churnside, J.; Ishimaru, A.; Freilikher, V.; Fuks, I.; Hill, R.; Irisov, V.; Kravtsov, Y.; Lataitis, R.; Mudaliar, S.; Ostashev, V.; et al.
ABSTRACT: On October 13, 2019 is the ninetieth birthday of the renowned physicist Professor Valerian I. Tatarskii. He is one of the founders of the international journal Waves in Random and Complex Media and its Associate Editor from 1991 to 1998. Outstanding seminal works of Professor V. I. Tatarskii made a global impact on physical science. The article describes main milestones of his life in science and his achievements in the theory of wave propagation in random media.